Climate variability and ecosystem response at long-term ecological research sites - Greenland, David, 1940-; Goodin, Douglas G. (Douglas Gard); Smith, R. C. (Raymond Calvin), 1934- (Long-Term Ecological Research Network series., 2003)
Presents the work that has been done and the understanding and database that have been developed by work on climate change done at the Long-Term Ecological Research (LTER) sites. This book pulls together information from all 20 research sites.